Staging of newly diagnosed Ewing sarcoma: Results of bone marrow aspiration and biopsy versus (18)FDG-PET/CT imaging for bone marrow involvement. (January 2023) - Guinot, A.; Tabone-Eglinger, S.; Isnardi, V.; Bahri, H.; Surdez, D.; Delattre, O.; Pierron, G.; Villemeur, M.; Lapouble, E.; Brahmi, M.; Bouhamama, A.; Corradini, N.; et al.
Abstract: Background: Ewing sarcoma (ES) is an aggressive bone or extraosseous tumour with an unfavourable prognosis when bone marrow metastases are present at diagnosis. The gold standard diagnosis for bone marrow (BM) involvement is cytological and pathological analysis through bone marrow aspiration and biopsy (BMAB). Several recent studies suggest that these invasive and painful procedures could be replaced by 18F-fluorodeoxyglucose-positron emission tomography/computed tomography ((18)FDG-PET/CT), as this nuclear imaging technique is highly sensitive at detecting bone and extraosseous metastases of ES. Methods: In order to study the precision of (18)FDG-PET/CT in the evaluation of bone marrow metastases at diagnosis, we compared the imaging results with cytological/histological analyses performed on BM samples. We retrospectively studied 180 patients with ES recorded at the Léon Bérard Centre over the past 10 years, who were evaluated by (18)FDG-PET/CT and BMAB at diagnosis. Results: Of the 180 patients, 13 displayed marrow metastases by cytological/histological examination, and only one of these did not have (18)FDG-PET/CT signs of bone marrow involvement, whereas the 167 remaining patients without marrow metastasis all had a negative (18)FDG-PET/CT, except for one. Hence, the sensitivity and specificity of (18)FDG-PET/CT in these patients was 92.3% and 99.4%, respectively. The overall survival at five years of all patients was 67.4% but decrease to 38.5% in the group with bone marrow metastases. Conclusion: Given the results presented herein the bone sarcoma group of the French Sarcoma Group suggests that invasive BMAB no longer be systematically performed for the staging at the diagnosis of ES. Graphical abstract: Image 1 Highlights: The gold standard for BMM diagnosis in ES is cytological analysis through BMA. 18)FDG-PET/CT is increasingly used for cancer staging at diagnosis. 18)FDG-PET/CT sensitivity and specificity for BMM diagnosis are 92.3% and 99.4%. Our group suggests that (18)FDG-PET/CT could replace BMA for initial staging. No longer performing routine BMA represents a significant health cost saving.